2008
DOI: 10.2754/avb200877030347
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Antioxidant and Detoxifying Enzymes in Rats after Lead Exposure

Abstract: Abstractalghazal m. a., V. lenártová, K. holovská, a. sobeková, m. falis, j. legáth: activities of antioxidant and Detoxifying enzymes in rats after lead exposure. acta Vet. brno 2008, 77: 347-354. the studies were undertaken to investigate the activity response of the antioxidant enzyme superoxide dismutase (soD) and detoxifying enzyme glutathione-s-transferase (gst) of rats exposed to lead. enzyme activities were determined in the liver, kidneys and heart of male and female rats that received 100 mg and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Alghazal et al (2008) reported an increase in GST following exposure to inorganic Pb. Consequently, increased levels of GST and GSH, the substrate for GST, may result from Pb-generated injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Alghazal et al (2008) reported an increase in GST following exposure to inorganic Pb. Consequently, increased levels of GST and GSH, the substrate for GST, may result from Pb-generated injuries.…”
Section: Discussionmentioning
confidence: 99%
“…There is an association between CVD, inflammation and oxidative stress (Roshan et al, 2011). Lead (Pb) is a non-essential toxic heavy metal widely distributed in the environment; various physiological, biochemical and behavioral dysfunctions are induced by chronic exposure to low levels of pb (Ahamed and Siddiqui, 2007;Alghazal et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…of prooxidant and antioxidant balance by generation of reactive oxygen species (ROS) (Alghazal et al, 2008;Roshan et al, 2012). Adipokines such as apelin, Creactive protein (CRP), tumor necrosis factor TNF-α and E-selectin represent a family of proteins released by adipocytes that affect various biological processes including metabolism, satiety, inflammation and cardiovascular function (Gaeini et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in agreement with the results obtained by Valverde, Trejo, and Rojas (2001) and Marchlewicz et al (2007), suggesting induction of Pb cytotoxicity by indirect mechanisms. Evidence of a dose response relationship between Pb exposure and LPO levels in cardiac tissue was previously reported (Alghazal et al 2008).…”
Section: Discussionmentioning
confidence: 79%
“…The elevated lipid hydroperoxides in liver, kidney and spleen observed in the current study in Pb and/or CPMtreated group are indicative of membrane damage due to formation of free radicals or through exhaustion of antioxidants, leading to oxidative stress. Lead is known to induce oxidative damage in various tissues (Jackie, Haleagrahara, and Chakravarthi 2011;Hamadouche et al 2009;Alghazal et al 2008;Abdel-Moneim, Dkhil, and Al-Quraishy 2011). These findings are in agreement with the results obtained by Valverde, Trejo, and Rojas (2001) and Marchlewicz et al (2007), suggesting induction of Pb cytotoxicity by indirect mechanisms.…”
Section: Discussionmentioning
confidence: 99%